Molecular analyses of unselected head and neck cancer cases demonstrates that human papillomavirus transcriptional activity is positively associated with survival and prognosis. Issue 1 (December 2016) - Masterson, Liam; Winder, David; Ball, Siolian; Vaughan, Katie; Lehmann, Martin; Scholtz, Lars-Uwe; Sterling, Jane; Sudhoff, Holger; Goon, Peter
Abstract Background Human papillomavirus DNA detection in head and neck squamous cell carcinoma has been linked to improved patient prognosis. The main aims of the study was to test the hypotheses that HPV16 E6/E7 oncogene and p53 function within tumours were associated with the widely reported improved patient survival and prognosis in head and neck cancer. Methods HPV16 DNA, mRNA and p53 mRNA presence were analysed in a prospective study of 42 unselected HNSCC patients; correlating the data with patient age, tumour staging/grade, treatment response, disease recurrence and survival. Results HPV16 DNA and HPV16 mRNA were present in 45.2 % and 21.4 % of patients, respectively. There was a significant positive association between the detection of HPV16 E6/E7 mRNA and p53 mRNA (p  = 0.032), but this was not replicated for HPV16 DNA. Five-year disease free survival for the whole cohort was 63 % (CI 52.5–73.5 %). Multivariable analysis revealed only HPV16 E6/E7 mRNA expression to have significant prognostic influence (p  = 0.04). Conclusions Our study suggests that HPV16 oncogenic transcriptional activity within HNSCC tumours is associated with improved patient survival and better prognosis in a German population. Simple HPV DNA detection alone did not demonstrate this association. The significant association of full-length (wild-type) p53 with HPV16 E6/E7 mRNA is further evidence for a functional relationship, which could contribute to the widely reported improved survival and prognosis. Larger studies are required to validate the frequency of HPV16 mRNA expression in HNSCC.